Desenvolvimento de sistema de iluminação solar com fibras ópticas - Rodrigues, Igor Vital (2018)
The development of the solar lighting system aims to illuminate internal environment using concentrated sunlight guided through optical fibers. Unlike existing systems, this model uses only one motor to move, do not use the brightness sensors to locate the sun and have only one lens for a bundle of optical fibers. A smart algorithm is implemented in a microcontroller to control a single motor, without the need of brightness sensors, so the lens always points to the sun maximizing system efficiency. A study of the solar concentration shows the limit that the fiber bundle supports without exceeding the maximum temperature indicated by the manufacturer. Infrared filters had their characteristics studied and the most appropriate was used in the prototype with the objective of reducing the heating of the fibers. Two luminaires were developed with one designed to illuminate diffusely and uniformly, and another in a focused and concentrated way. In diffuse the fibers were modified to allow light to escape from the side of the fibers and a comparative evaluation of the light distribution performance of each of the modifications made is shown. The results show the system's ability to track the sun, the distribution of light by each luminaire, the spectrum of light provided by the system, and the amount of light the system is able to provide. The system delivers 1,850 lumens in a beam of 120 plastic optical fibers 7 meters long.